Influence of age on real-life effects of doxycycline for acute exacerbations among COPD outpatients: a population-based cohort study. Issue 1 (18th February 2020) - Wang, Yuanyuan; Bos, Jens H; Boezen, H Marike; Alffenaar, Jan-Willem C; van Boven, J F M; Schuiling-Veninga, Catharina C M; Wilffert, Bob; Hak, Eelko
Abstract : Introduction: Although bacteria contribute significantly to acute exacerbations of chronic obstructive pulmonary disease (AECOPD), the added value of antibiotics remains controversial, especially in outpatient settings. Age may affect antibiotic effectiveness, but real-world evidence is lacking. We aimed to assess the influence of age on the effectiveness of doxycycline for AECOPD. Methods: A retrospective cohort study among outpatients with the first recorded AECOPD treated with oral corticosteroids was conducted using a large pharmacy dispensing database. The primary outcome was treatment failure within 15–31 days after treatment start. Secondary outcome was time to second exacerbation. All analyses were stratified by age groups. Results: We identified 6300 outpatients with the first AECOPD. 2261 (36%) received doxycycline and 4039 (64%) did not receive any antibiotic (reference group). Overall, there was no difference in treatment failure (adjusted OR: 0.97, 95% CI: 0.84 to 1.12) between two groups. Similarly, no difference in treatment failure was observed in younger groups. However, in patients with advanced age (≥75 years), treatment failure was significantly reduced by doxycycline compared with reference (16% vs 20%, adjusted OR: 0.77, 95% CI: 0.62 to 0.97). Overall, median time to second exacerbation was 169 days (95% CI: 158 to 182 days) in doxycycline group compared with 180 days (95% CI: 169 to 191 days) in reference group (adjusted HR: 1.06, 95% CI: 0.99 to 1.12). Although in older patients there was a trend within 3 months towards longer time of next exacerbation by doxycycline, it did not achieve statistical significance. Conclusions: Our findings showed short-term treatment benefit of doxycycline added to oral corticosteroids for chronic obstructive pulmonary disease patients with advanced age. This value remains unclear for persons aged under 75 years in current primary care. Long-term preventive benefits of doxycycline for the next exacerbation were not observed, irrespective of age.